QCM and AFM analysis of anticoagulant activities of sulfonated polymers against fibrin formation - Jung, Hyosook (Langmuir : the ACS journal of surfaces and colloids, 2009)
Quartz crystal microbalance (QCM) and atomic force microscope (AFM) were utilized to investigate the anticoagulant activities of sulfonated polymers against fibrin formation. Quantitative data on the thickness and viscoelastic properties of coagulated fibrin layers formed at various concentrations of sulfonated polymers were obtained from QCM results by applying a Voight-based model. Four types of sulfonated polymers including sulfonated chitosan (S-chitosan), monosulfonated poly(ethylene oxide) (PEO-SO(3)), disulfonated PEO (PEO-2SO(3)), and 4-arm sulfonated PEO (PEO-4SO(3)) were studied to compare with heparin in the presence or in the absence of antithrombin III (AT). All the sulfonated polymers showed the heparin-like activities to inhibit the function of thrombin for fibrin formation in the more or less extent while chitosan and PEO did not. Especially, S-chitosan prepared by sulfonation with propane sultone under a mild condition exhibited 35% of activity of free heparin while sulfonated PEOs showed 5-12% of heparin. However, there was no effect of S-chitosan without AT, indicating that the S-chitosan interfered in the fibrin formation process mainly by AT-mediated inhibition against thrombin. The sulfonated polymers not only decreased the coagulated mass but also affected the surface architecture and viscoelastic properties of the final fibrin layers coagulated. With increasing the concentrations of heparin or heparin-like polymers, the thick and textured fibrin layer was gradually diminished to reveal the thin and rigid fibrinogen-adsorbed layer, and therefore the fibrin layer became more rigid. The surface architecture of fibrin layers was confirmed by AFM. With increasing anticoagulants the density of both fibrin fiber and junctions between fibers was decreased but the fiber diameter was not much reduced